2006
DOI: 10.1111/j.1525-1497.2005.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Low Literacy and Social Support in Predicting the Preventability of Hospital Admission

Abstract: While low literacy was not predictive of admission preventability, the formal assessment of alcohol binge drinking, social support for medical care, social network size, and prior outpatient utilization may enhance our ability to predict the preventability of hospitalizations and develop targeted interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 36 publications
2
23
1
Order By: Relevance
“…A cross sectional study evaluating low literacy as a predictor of PPH, when considered in the context of social support, sociodemographics, health status, and risk behaviours, found that neither low literacy (< seventh grade) nor very low literacy (< fourth grade) was significantly associated with preventability of hospitalisation [45]. The authors found that significant predictors of PPH included binge alcohol drinking, lower social support for medical care, annual clinic visits, and less social networks.…”
Section: Demographics and Socioeconomic Statusmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross sectional study evaluating low literacy as a predictor of PPH, when considered in the context of social support, sociodemographics, health status, and risk behaviours, found that neither low literacy (< seventh grade) nor very low literacy (< fourth grade) was significantly associated with preventability of hospitalisation [45]. The authors found that significant predictors of PPH included binge alcohol drinking, lower social support for medical care, annual clinic visits, and less social networks.…”
Section: Demographics and Socioeconomic Statusmentioning
confidence: 99%
“…Five additional studies from the USA [45][46][47][48][49] and 1 Australian study [44] were identified in the search to update the 2 identified literature reviews. The studies are predominantly about socioeconomic factors, or focus on uninsured populations or rurality.…”
Section: Update Of Literature Reviews: 2005-june 2009mentioning
confidence: 99%
“…Inpatients with mental disorders (including substance use disorders) were significantly more likely than other admitted inpatients to have been admitted for an ACSC and also had longer average length of stay. Another study with a mixed-age inpatient sample found that binge drinking (five or more alcoholic beverages per occasion during the past 30 days) was predictive of preventable hospitalization (Arozullah et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, although inpatient care of such patients probably does not differ from the average, 6 this population is at high risk for poor health outcomes. as illustrated by factors such as suboptimal chronic disease management, 7 preventable hospitalization, 8 and increased mortality. 9,10 Remission involves a major behavior change that has been conceived of as a progression of stages, including precontemplation, contemplation, preparation, action, and maintenance.…”
Section: Abstract: Alcoholism Inpatient Health Behaviormentioning
confidence: 99%
“…The Recognition scale is composed of 7 items (score range 7-35) that estimate an individual's recognition of his or her alcohol use as an important problem, desire to change, and perception of harm related to drinking. The Ambivalence scale contains 4 items (score range [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] that ask respondents if they wonder if they are alcoholic, drink too much, are hurting others, and are in control of their drinking. Degree of wondering (as opposed to knowing) about such issues is considered a reflection of uncertainty, or ambivalence, and higher scores suggest that the patient is at a more contemplative stage of change.…”
Section: Process Of Change Variablesmentioning
confidence: 99%